(untitled) (Bioscience Journal, 2020)
There is an increased interest in the consumption of healthier and innovative meat products. This study aimed to produce lamb burgers by replacing pork fat by peach palm by-product flour – PPF. The burgers were produced with lambs that had a safflower seed-supplemented diet. The PPF was added at levels of 0% (H0), 3% (H3), 6% (H6) and 9% (H9) in the substitution of fat. The flour produced with peach palm by-product showed high fiber content (63.9%) and high capacity of water absorption (8.1 g.g-1) and oil absorption (3.8 g.g-1). The PPF addition increased the cooking yield (68.2 - 77.0%), moisture retention (38.5 - 43.4%) and dietary fiber content (3.2 - 7.0%) in relation to H0, while the color parameters were similar among the formulations. The sensorial attributes overall appearance and aroma did not differ (p>0.05) in the lamb burgers produced, but the highest scores for flavor, texture and purchase intention were observed for H0, H3 and H6. PPF addition to lamb burgers increased the hardness values, and it did not affect elasticity and cohesiveness. The microbiological parameters showed that the formulations are safe for consumption. Therefore, PPF can be considered a low-cost alternative to nutritional enrichment of lamb burgers, being the level of 6% the most recommended due to the sensorial acceptance.